Hukum Perkawinan dan Tantangan Sosial Kontemporer: Studi atas Perkawinan mut’ah di Indonesia - Ahmad Shohibul Hikam; Noor Muhamad Shaddad; Muhamad Zaky Akbar Faridi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This article examines the dynamics of marriage law in Indonesia, focusing on the practice of mut'ah marriage, a form of temporary marriage known in the Shia tradition. Although not recognized in Indonesia's national legal system, which is based on Sunni Islamic law and positive law, this practice continues to occur on a limited basis in some communities. This study aims to examine the legal position of mut'ah marriage within the Indonesian legal framework and explore the contemporary social challenges it poses, such as social stigma, women's vulnerability, and potential legal conflicts. The approach used is qualitative, with normative analysis of laws and regulations, as well as social review through case studies and limited interviews. The results of the study indicate tensions between religious norms, state law, and social practices, which demand a more inclusive and equitable policy response. This article recommends the need for open dialogue between Islamic schools of thought and the affirmation of legal protections for vulnerable parties in unrecognized marriage practices.